Isolation, social support, and COVID-19-burnout among college students in a university in eastern China - Song, Yan; Li, Huizi; Song, Yuxin; Song, Gexuan; Su, Qing; Liu, Na; Zheng, Zheng; Sun, Yueyi (Frontiers in Psychology, 2025)
BackgroundTo cope with the COVID-19, social isolation applied by countries around the world. These measures have significantly impacted public health, particularly among Chinese college students. Considering the significant impact of social isolation on social support, and the important value of social support for mental health, this study aims to explore the effects of social isolation on the mental health of Chinese college students during the pandemic.MethodsThe Social Support Scale, COVID-19-burnout Scale Questionnaire, and Brief Symptom Checklist were used in this survey. In November 2022, a total of 394 college students voluntarily participated in this survey. And 70.3% of them were female, mean age = 19.09 ± 0.82 years), with 31.0% (n = 122) isolated and 69.0% (n = 272) non-isolated.Results(1) Compared with the non-isolated group, the isolated group of college students scored significantly lower on social support (t = −3.40, p < 0.01), higher on COVID-19-burnout (t = 2.42, p < 0.01) and psychological distress (t = 2.96, p < 0.01); (2) Significant negative correlations emerged between social support and COVID-19-burnout (r = −0.142, p < 0.01), as well as psychological distress (r = −0.356, p < 0.01); (3) Within-family social support correlated negatively only with psychological distress (r = −0.314, p < 0.01), whereas outside-family social support was negatively associated with both COVID-19-burnout (r = −0.157, p < 0.01) and psychological distress (r = −0.339, p < 0.01). (4) Isolation moderated the relationship between social support and COVID-19-burnout (β = −0.213, p < 0.01; interaction β = 0.198, p < 0.01), but not social support and psychological symptoms (p = 0.26).ConclusionThis study found the negative impacts of social isolation and positive influence of social support during COVID-19 on the mental health and COVID-19-burnout of college students. It also highlights the influence of extra-family social support in reducing psychological distress and COVID-19-burnout. And isolation was found acted as a significant variable between social support and COVID-19-burnout. These results provide a new insight for understanding the mechanism through which social support impacts the mental health, and suggesting tailored interventions for Chinese college students in the context of COVID-19. The cultural characteristics during the isolation process and some limitations of this research were discussed also.